Respiratory Aspergillus Colonization Was Associated With Relapse of Acute Exacerbation in Patients With Chronic Obstructive Pulmonary Disease: Analysis of Data From A Retrospective Cohort Study - Wu, Yi-xing; Zuo, Yi-hui; Cheng, Qi-jian; Huang, Yi; Bao, Zhi-yao; Jin, Xiao-yan; Gao, Xi-wen; Tu, Chun-lin; Hu, Wei-ping; Hang, Jing-qing; Wang, Wei-qin; Zhang, Feng-ying; et al. (Frontiers in Medicine, 2021)
Background: Patients with chronic obstructive pulmonary disease (COPD) are more susceptible to Aspergillus colonization or infection. Several studies have demonstrated that invasive pulmonary Aspergillosis (IPA) and Aspergillus hypersensitivity (AH) have a detrimental effect on COPD. However, it remains to be clarified whether Aspergillus colonization is associated with acute exacerbation of COPD (AECOPD). This study aimed to explore the impact of Aspergillus colonization in the lower respiratory tract on AECOPD. Method: Patients with Aspergillus colonization were identified from a retrospective cohort of hospitalized AECOPD from 2011 to 2016 in 8 centers in Shanghai, China. The demographic information, conditions of the stable stage, clinical characteristics during hospitalization, and 1-year follow-up information after discharge were collected and compared to participants without fungi colonization. Result: Twenty-six hospitalized AECOPD patients with Aspergillus colonization and 72 controls were included in the final analysis after excluding patients with other fungi isolation and matching. The rates of recurrence of acute exacerbation within 90 days and 180 days after discharge in the patients with Aspergillus colonization were both significantly higher than that in the fungi negative patients (90 days: 19.2% vs. 4.2%, p = 0.029; 180 days: 23.1% vs. 4.2%, p = 0.010), and the all-cause mortality within 1 year was also higher (11.5% vs. 0.0%, p = 0.017). Multivariate logistic regression analysis showed that Aspergillus colonization was an independent risk factor for the recurrence of acute exacerbation within 90 days and 180 days (90 days: OR = 8.661, 95% CI: 1.496-50.159, p = 0.016; 180 days: OR =10.723, 95% CI: 1.936-59.394, p = 0.007). Conclusion: Aspergillus colonization may predict poor prognosis of AECOPD while leading to an increased risk of recurrent AECOPD in a short period.